Pemanfaatan Multimedia Interaktif Sebagai Sarana Inovasi Pembelajaran Di Sekolah Dasar Pada Era Digital - Ni Putu Diah Puspita Dewi; Ni Putu Candra Prastya Dewi; I Ketut Ngurah Ardiawan (Prodi Pendidikan Guru Sekolah Dasar, 2026)
The integration of digital technology in elementary education has become essential to enhance learning quality in the digital era. However, classroom practices remain predominantly conventional, limiting student engagement and higher-order thinking development. This study aims to systematically analyze the effectiveness and pedagogical implications of interactive multimedia as a learning innovation tool in elementary schools. This research employed a structured literature review by analyzing ten peer-reviewed articles published between 2022–2026, selected through databases such as Google Scholar and national indexed journals (SINTA). The inclusion criteria focused on empirical studies examining interactive multimedia in elementary education, while irrelevant and non-peer- reviewed sources were excluded. Data were analyzed using content analysis and thematic synthesis. The findings indicate that interactive multimedia significantly improves learning motivation, student engagement, conceptual understanding, critical thinking skills, digital literacy, and academic achievement. Furthermore, interactive multimedia provides visual and experiential learning environments aligned with students’ cognitive development. The novelty of this study lies in its integrative synthesis across multiple multimedia forms and subjects, offering a comprehensive framework for understanding effectiveness patterns and design implications. However, its implementation is influenced by instructional design quality, teacher digital competence, and technological infrastructure. Therefore, interactive multimedia should be positioned not only as a technological tool but as a pedagogical strategy for enhancing elementary education in the digital era.